2002
DOI: 10.1073/pnas.032089399
|View full text |Cite
|
Sign up to set email alerts
|

Iron uptake in ferritin is blocked by binding of [Cr(TREN)(H 2 O)(OH)] 2+ , a slow dissociating model for [Fe(H 2 O) 6 ] 2+

Abstract: Ferritin concentrates iron as a hydrous ferric oxide in a protein cavity (8 nm in diameter) by using eight pores along the threefold symmetry axes of the octahedral supramolecular structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 54 publications
0
24
0
Order By: Relevance
“…B, Rate sensitivity when the C/D loop is manipulated at ion pair arginine 72 and aspartate 122, and by increasing the C/D loop size by inserting a second set of the same loop amino acids, with all the wild type gating residues present. Data from reference [9]. Temperature effects on global structure were measured at 280 nm (UV absorbance) and on pore structure at 280 nm (circular dichroism), as described in reference [3], using recombinant, mineralized ferritins in 0.015M MOPS, pH = 7.…”
Section: Summary and Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…B, Rate sensitivity when the C/D loop is manipulated at ion pair arginine 72 and aspartate 122, and by increasing the C/D loop size by inserting a second set of the same loop amino acids, with all the wild type gating residues present. Data from reference [9]. Temperature effects on global structure were measured at 280 nm (UV absorbance) and on pore structure at 280 nm (circular dichroism), as described in reference [3], using recombinant, mineralized ferritins in 0.015M MOPS, pH = 7.…”
Section: Summary and Perspectivementioning
confidence: 99%
“…Current models of ferrous ion entry through the gated pores into the nanocage are based on competition with other metal ions [4][5][6][7][8][9], mutagenesis of non-gating residues around the pore [8,10], and co-crystal structures with metal inhibitors [11]. The model is weakened by the absence of crystal structures of the mutant proteins, by the multiple sites for metal inhibitor binding in addition to the pores, and by studies suggesting other ferrous ion entry sites besides the gated pores [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The diameter of fully hydrated Fe 2+ ions is 6.9 Å suggesting that in order for Fe 2+ to pass through ferritin ion channels, either partial/full dehydration of Fe 2+ •(H 2 O) 6 , protein channel conformational flexing/channel widening, or both is required, in order for the Fe 2+ substrate to reach the enzyme sites in ferritin [24]. Variable-temperature variable field (VTVH) magnetic circular dichroism (MCD) spectroscopy of Fe 2+ ions bound to ferritin enzymatic sites demonstrated that Fe 2+ in this environment is coordinated by only a single water molecule.…”
Section: Introductionmentioning
confidence: 99%
“…13 Chromium has been found to compete with Fe for binding to transferrin and impairs Fe metabolism and storage; in animals, the reduced Fe, Fe binding capacity, and ferritin correlated with reduced hemoglobin. 14,15 However, in children receiving parenteral nutrition, although elevated serum Cr was shown to correlate inversely with serum Fe, hemoglobin values did not diminish. 16 We are aware of a single animal study that found anemia that ameliorated with time with exposure to Cr.…”
Section: Discussionmentioning
confidence: 97%